Rapid Arabic Vol. 1. (Earworms musical brain trainer Variation: Earworms musical brain trainer., 2008)
By listening to those specially composed melodies with their rhythmic repetitions of Arabic and English a few times, you pick up over 200 essential words and phrases that will not just be on the tip of your tongue, but burned deeply into your long-term memory in next to no time.